Aplicación de contabilidad comercial en “Insufarm Distribuciones Médicas”, periodo junio-agosto del 2014 - Román Ruiz, Magali Alexandra (2015)
The development of the thesis entitled: "APPLICATION OF ACCOUNTING IN COMMERCIAL" INSUFARM MEDICAL DISTRIBUTIONS "PERIOD JUNE - AUGUST 2014 was held with the main purpose of applying the accounting process, in order to meet timely the real economic situation - Finances shop. In the development of the research were complied with the stated objectives; starting with the preparation of the Plan and Accounting Manual; I complying with regulations, legal accounting relevant and of course covering the financial needs of the business, so be codified and detail each of the ledger accounts used in the accounting process; the same that formed the basis for the development of the accounting process starting with the classification of source documents, then with the development of the Initial Inventory, State Initial Situation, where the assets, rights and obligations are there in the business registered , then developed into memorandum of operations used to record transactions in the journal in a chronological manner, then he proceeded to the Ledger, Trial Balance, to comply with the presentation of financial statements. Finally, conclusions and recommendations were developed, they allow to terminate the present research work developed by mentioning the main events where it is mainly recommended to keep the accounting system implemented; with the aim of improving profitability through new and better choices taken from the results